Storytelling in Chefchaouen Northern Morocco : an annotated study of oral performance with transliterations and translations - Rahmouni, Aicha. (Studies on Performing Arts & Literature of the Islamicate World, 2015)
Storytelling in Chefchaouen Northern Morocco includes two sets of tales told by two different storytellers with an annotated study of the oral performance, transliterations and translations. The purpose is to preserve a part of the region's oral tradition of storytelling in the vernacular language in which it has been transmitted, presenting the original texts with parallel English translation. In addition, the cultural, literary, and linguistic background necessary for understanding this body of oral performance is given. A combination of disciplines (anthropology, philology, sociolinguistics, dialectology, comparative literature, ethnography, typology) is applied to the linguistic and literary features of the present corpus.